(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The modern concept of education sets the goal of forming a personality capable of effective self-realization in the field of future professional activity. In this regard, the problem of the formation and development of students’ communicative competence in the process of learning a foreign language acquires special significance. The article examines the main issue of developing reading and speaking skills in foreign languages when studying fiction, since this is a key factor in the development of linguistic and sociocultural competence of foreign language learners.